2019
DOI: 10.1371/journal.pone.0223624
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the population history of the sandy beach amphipod Haustorioides japonicus using the calibration of demographic transition (CDT) approach

Abstract: Calibration of the molecular rate is one of the major challenges in marine population genetics. Although the use of an appropriate evolutionary rate is crucial in exploring population histories, calibration of the rate is always difficult because fossil records and geological events are rarely applicable for rate calibration. The acceleration of the evolutionary rate for recent coalescent events (or more simply, the time dependency of the molecular clock) is also a problem that can lead to overestimation of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Currently 10 species are recognized in the genus Haustorioides from East Asia (Jo 1988, Ogawa et al 2021. Ecological studies on these amphipods have been mostly concerned with H. japonicus whose geographic range extends from northern Kyushu to southern Hokkaido in Japan (Kamihira 1992, Sakuma et al, 2019. This species is a detritus and filter feeder (Kamihira 1992, Kogure & Takada 2012, Takamatsu & Yanai 2019, and inhabits in the swash zone of sandy beaches, burrowing into the surface layer of the sand substratum.…”
Section: Introductionmentioning
confidence: 99%
“…Currently 10 species are recognized in the genus Haustorioides from East Asia (Jo 1988, Ogawa et al 2021. Ecological studies on these amphipods have been mostly concerned with H. japonicus whose geographic range extends from northern Kyushu to southern Hokkaido in Japan (Kamihira 1992, Sakuma et al, 2019. This species is a detritus and filter feeder (Kamihira 1992, Kogure & Takada 2012, Takamatsu & Yanai 2019, and inhabits in the swash zone of sandy beaches, burrowing into the surface layer of the sand substratum.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, H. munsterhjelmi was reported from eastern Hokkaido (Kamihira 1992). Recently, Takada et al (2018) recognized five genetic clades among the populations of H. japonicus along the Japanese coast of Japan Sea, East China Sea and the northwestern Pacific, and Sakuma et al (2019) reported an additional population from Miyagi Prefecture. However, the taxonomic status of those clades still remains undetermined.…”
Section: Introductionmentioning
confidence: 99%